The bryophyte flora of the Cheremys’ky nature reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The bryophyte flora of the Cheremys’ky nature reserve (the Volyns’ka oblast’, NW Ukraine) includes 114 species of 67 genera, 42 families belonging to two divisions: Marchantiophyta (12 spp.) and Bryophyta (102 spp.). Among them, glacial relicts (Calliergon trifarium, Scorpidium scorpioides, Helodium blandowii) and rare taxa (Orthotrichum lyellii, Aulacomnium androgynum, Thuidium tamariscinum) are presented.
Keywords: bryophytes, Cheremys’ky nature reserve, Ukrainian Polissya.